2022
DOI: 10.26508/lsa.202201503
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive CD8 T cells in NOD mice exhibit phenotypic heterogeneity but restricted TCR gene usage

Abstract: Type 1 diabetes (T1D) is an autoimmune disorder defined by CD8 T cell–mediated destruction of pancreatic β cells. We have previously shown that diabetogenic CD8 T cells in the islets of non-obese diabetic mice are phenotypically heterogeneous, but clonal heterogeneity remains relatively unexplored. Here, we use paired single-cell RNA and T-cell receptor sequencing (scRNA-seq and scTCR-seq) to characterize autoreactive CD8 T cells from the islets and spleens of non-obese diabetic mice. scTCR-seq demonstrates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 106 publications
1
4
0
Order By: Relevance
“…Although we observed greater amounts of "medium" (0.001 < X < 0.01) and reduced levels of "small" (1e -4 < X < 0.001) expanded clone cutoffs following anti-CD226 treatment (Figure 7C), we did not observe any significant differences in the overall abundance of small and medium expanded clones by cell cluster (Figure 7D-F). Using previously reported CDR3 sequences [39], we found that most IGRP 206-218 -reactive T cells were localized to the activated CD8 + T cell cluster (Figure 7G).…”
Section: Cd226 Blockade Regulates T Cell Clonal Expansionsupporting
confidence: 54%
See 1 more Smart Citation
“…Although we observed greater amounts of "medium" (0.001 < X < 0.01) and reduced levels of "small" (1e -4 < X < 0.001) expanded clone cutoffs following anti-CD226 treatment (Figure 7C), we did not observe any significant differences in the overall abundance of small and medium expanded clones by cell cluster (Figure 7D-F). Using previously reported CDR3 sequences [39], we found that most IGRP 206-218 -reactive T cells were localized to the activated CD8 + T cell cluster (Figure 7G).…”
Section: Cd226 Blockade Regulates T Cell Clonal Expansionsupporting
confidence: 54%
“…To identify IGRP-reactive T cells, the TCR-and TCR-β CDR3 sequences were compared to the CDR3 sequences of NOD IGRP 206-124 -specific CD8 + T cells previously described by Kasmani et al [39] using the Biostrings package (version 2.68.1). CDR3 sequences within one amino acid mismatch of either the TCR-or TCR-β chain of the previously published sequences were mapped as IGRP-reactive.…”
Section: Tcr Repertoire Analysis and Mapping Of Igrp-reactive Clonotypesmentioning
confidence: 99%
“…The use of scRNA-seq for identifying autoimmune disease-related immune repertoires has only recently emerged, including type 1 diabetes (T1D) ( Linsley et al, 2021 ; Kasmani et al, 2022 ), autoimmune hepatitis (AIH) ( Renand et al, 2020 ), primary SjD (pSjD) ( Hong et al, 2020 ; Hou et al, 2022 ), and systemic lupus erythematosus (SLE) ( Smita et al, 2022 ) ( Table 3 ). Not only is it a direct study of the disease itself, but scTCR-seq has also been used to study T cell populations and/or related mechanisms closely associated with autoimmune disorders, allowing us to visualize the immune repertoire expressed by several cell subpopulations.…”
Section: Development Of Rna Sequencing (Rna-seq) Technology To Identi...mentioning
confidence: 99%
“…Not only is it a direct study of the disease itself, but scTCR-seq has also been used to study T cell populations and/or related mechanisms closely associated with autoimmune disorders, allowing us to visualize the immune repertoire expressed by several cell subpopulations. In spondyloarthritis (SpA) patients, arthritogenic peptides are presented by the risk allele HLA-B*27 to antigen-specific CD8 + T cells to initiate or maintain an autoimmune response, Deschler et al (2022) used scTCR-seq to analyze CD8 + T cells in the patient's synovial fluid (SF) and revealed a preferential expansion of the TCR TRAV-and TRBV-families, common motifs in the CDR3 loop and identical TCR chains across patients. Follicular helper T cells are central regulators of germinal centers and contribute to the formation of pathogenic autoantibodies, Akama-Garren et al The read length of RNA-seq is much shorter than that of firstgeneration sequencing (e.g., Sanger sequencing), and scRNA-seq data often contain many missing values or dropouts due to the failure to amplify the original RNA input, this frequency depends mainly on the protocol.…”
Section: Introductionmentioning
confidence: 99%
“… 14 However, recent advances in single-cell technologies are making it possible to characterise diabetogenic T cells in high-dimensional phenotypic, transcriptional, and epigenetic detail. 38 This might eventually lead to the discovery of accurate and sensitive immunological biomarkers.…”
Section: Immune Pathogenesismentioning
confidence: 99%